Application of third-generation sequencing to herbal genomics - Gao, Longlong; Xu, Wenjie; Xin, Tianyi; Song, Jingyuan (Frontiers in Plant Science, 2023)
Traditional medicine has been used to protect human health for thousands of years. However, the genetic information of organism-derived species is still extremely rare, and the exploitation of natural resources is, therefore, limited. The application of third-generation sequencing (TGS) techniques has brought us a great opportunity to gather invaluable genetic information and promote the development of herbal genomics. In this review, we introduce two main TGS techniques, PacBio SMRT technology and Oxford Nanopore Technology, and compare the two techniques with Illumina, the predominant next-generation sequencing technique. In addition, we summarize nuclear and organelle genome assemblies of commonly used medicinal plants and choose several examples from genomics, transcriptomics, and molecular identification studies to dissect the specific processes and summarize the advantages and disadvantages of the two TGS techniques when applied to medicinal organisms. Finally, we describe how we expect that in the future, TGS techniques will be widely utilized to assemble telomere-to-telomere (T2T) genomes and the epigenomics research of medicinal plants.